Basic construction of the flat angle calibration test bench for geodetic instruments - Bručas, Domantas; Giniotis, Vytautas; Petroškevičius, Petras (Geodesy and Cartography, 2012)
In our days precise geodetic instruments are very widely used in geodesy, building structures, surveying, machine engineering etc. Many of those instruments are based on precise measurement of the directions differences (ie measurement of angles). Such instruments are: theodolites, digital theodolites, total stations etc. Testing and calibration of these instruments is quite complicated task, although it is evidently needed. In this paper we present the creation and preliminary research of accuracy of the test bench designed to perform the testing and calibration of such geodetic instruments.Stendo geodezinių prietaisų plokščiajam kampui kalibruotiSantrauka. Pastaruoju metu tikslūs geodeziniai prietaisai yra plačiai naudojami geodezijoje, statyboje, topografijoje, mašinų gamyboje it t. t. Daugumos šių prietaisų veikimo principas pagrįstas tiksliu kampų matavimu. Tokie prietaisai – teodolitai, elektroniniai tacheometrai ir kt. Atlikti šių prietaisų patikrą ir kalibruoti – gana sudėtingas techninis uždavinys. aprašomas naujai sukurtas įrenginys tokiems geodeziniams prietaisams kalibruoti ir tikrinti, jo kūrinio eiga bei pradiniai tikslumo tyrimai.First published online: 03 Aug 2012